Error pattern analysis of the Mathematics problem solving of grade 10 learners - Campanilla, Norveen S.; Mendoza, Claire R. (Journal of Social, Humanity, and Education, 2024)
Purpose: This study investigates respondents' error patterns in mathematics problem-solving, their impact on problem solving, and their attitudes towards mathematics, examining the relationship between these factors. Research methodology: This study used a convergent mix method design to analyze data from 80 Grade 10 students at Matucay National High School, focusing on error patterns in problem solving and the relationship between learners' performance and their attitudes towards mathematics. Results: The study revealed that students excel in problem solving in mathematics, but their errors are mainly in formulation. They need to improve their reading comprehension, conceptual knowledge, and reasoning skills. The study also found that students' attitudes towards mathematics were influenced by their sex but not their problem-solving performance. Limitations: The study involved grade 10 students, and the findings may be different if participants were at a different grade level (e.g., grade 8, grade 9, etc.). In addition, other disciplines of mathematics problem-solving can also be explored for the comparison of results. Contribution: Enhances the understanding of the relationship between students’ attitudes towards mathematics and error patterns committed in calculating mathematics problem-solving. Emphasizing integrating the relative day-to-day experience of students and engaging in activities to boost motivation and learning outcomes is useful in shaping effective strategies for students, teachers, administrators, and officials. Novelty: This study emphasizes the significance of real-world experiences in mathematics problem-solving to improve learning outcomes and attitudes, offering valuable insights for educators, administrators, policymakers, and students in developing effective learning strategies and highlighting the connection between positive attitudes and mathematical problem-solving experiences.